Cyber-Physical Systems: Intelligent Models and Algorithms - Kravets, Alla G.; Bolshakov, Alexander A.; Shcherbakov, Maxim; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is devoted to intelligent models and algorithms as the core components of cyber-physical systems. The complexity of cyber-physical systems developing and deploying requires new approaches to its modelling and design. Presents results in the field of modelling technologies that leverage the exploitation of artificial intelligence, including artificial general intelligence (AGI) and weak artificial intelligence. Provides scientific, practical, and methodological approaches based on bio-inspired methods, fuzzy models and algorithms, predictive modelling, computer vision and image processing. The target audience of the book are practitioners, enterprises representatives, scientists, PhD and Master students who perform scientific research or applications of intelligent models and algorithms in cyber-physical systems for various domains.
Bio-inspired modelling -- Fuzzy models and algorithms -- Predictive modelling -- Computer Vision and Image Processing.
Keywords: Cooperating objects (Computer systems).; Computational intelligence; Engineering -- Data processing; Cyber-Physical Systems; Computational Intelligence; Data Engineering; Cooperating objects (Computer systems); Artificial intelligence; Fuzzy mathematics; Machine learning